IMPLEMENTATION OF DISCRETIONARY RIGHT OF THE ADMINISTRATIVE BODY IN GEORGIA IN CASES OF CONSTRUCTION LAW VIOLATIONS AND THEIR COURT CONTROL (Law and world, 2018)
Present-day governance has to solve more complicated and varied tasks for which in certain cases it is equipped by the government with the discretionary right – certain freedom to make decisions, which is expressed in the fact that the administrative body is authorized to select itself the most suitable decision out of several alternatives to achieve the aim. The article discusses the importance of the institutions of the discretionary right and their place in the legislative systems of various countries. Special attention will be given to several legislative regulations in Georgia in respect with the discretion institute and difficulties of their implementation in administrative and court practice.